Advertisement

- F
Formula

We multiply the fractions so that the second fraction numbers are in inverse (mean: the first fraction remained the same, the second fraction reversed, the numerator becomes denominator and the denominator becomes numerator).

a b ÷c d =a x d b x c Example:

4 6 ÷6 12 - 1
Reverse the numbers of the second fraction, then multiply the numerators together and the denominators together.

4 6 ÷6 12 =4 x 12 6 x 6 =48 36 - 2
Simplify the fraction if possible

more about Simplifying click here48 36 =48 ÷ 12 36 ÷ 12 =4 3

Advertisement